Quantitative models for participation evaluation in community development: a theoretical review - Zomorrodian, Amir Hossein; Gill, Sarjit Singh; Abu Samah, Asnarulkhadi; Ahmad, Nobaya (IDOSI Publications, 2013)
This article is an interdisciplinary review of the issue of participation evaluation. It is our contention that each and every scale and model developed to measure participation in community development approach falls under either the theory of empowerment or the theory of participatory democracy. The article also provides a detailed summary of prominent models for participation evaluation in community development practices with regard to socio-political theories supporting these models. In addition, both the weak and strong points of each model are discussed and a number of suggestions and implications for providing a comprehensive understanding of the participation issue are provided.